1993
DOI: 10.1103/physrevb.47.574
|View full text |Cite
|
Sign up to set email alerts
|

Electrical noise from spins inFe1xZr

Abstract: In films of a-Fel "Zr with x =0.08 two distinct transitions were found in the electrical noise. A high-temperature transition produced a regime of strongly magnetic-field-dependent noise showing non-Gaussian effects, as would be expected at the ferromagnetic transition. Observations of single-domain switching events give a direct estimate of a dynamical coherence length, large enough to show true ferromagnetism in the films. At lower temperature, a sharp, field-dependent rise in noise appeared near the suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…21 In metals, such processes are usually related to thermally activated motion of structural defects disturbing the effective cross section of the electron scattering centers. Currently, the notion of superposition of thermally activated processes coupled to the resistivity is widely invoked to explain the origin of the 1/f noise, and this in many different systems: metals, 21,30,33 semiconductors, 34-37 magnetic materials, 38,39 superconductors in the normal state, 40,41 etc.…”
Section: Theoretical Background and Discussionmentioning
confidence: 99%
“…21 In metals, such processes are usually related to thermally activated motion of structural defects disturbing the effective cross section of the electron scattering centers. Currently, the notion of superposition of thermally activated processes coupled to the resistivity is widely invoked to explain the origin of the 1/f noise, and this in many different systems: metals, 21,30,33 semiconductors, 34-37 magnetic materials, 38,39 superconductors in the normal state, 40,41 etc.…”
Section: Theoretical Background and Discussionmentioning
confidence: 99%
“…We have found that another transport phenomenon-low-frequency resistance noise from slow dynamics in the spin-glass phase-appears to be found quite generally in conducting spin glasses, so that it offers a promising probe of spin-glass dynamics in single-layer films. [10][11][12] In this article, we demonstrate that noise technique are suit-able for measuring finite-size effects on the spin dynamics near the spin-freezing temperature, T f .…”
Section: Introductionmentioning
confidence: 89%
“…Since we observe a decrease of the resistance noise when a magnetic field is applied in the 10K − 30K range (a factor of 0.6 at B= 7T and at T= 15K, see the inset of fig.7), a spincoupling origin of this noise can be suggested. The blocking of magnetic fluctuations at low temperature with non Arrhenius slowing down makes think of spin glasses [29]. Note, however, that some spin glasses do not show a decrease but a growing of noise at low temperature due to UCF coupling [30].…”
Section: Noise Measurements As a Complementary Toolmentioning
confidence: 99%
“…7), a spincoupling origin of this noise can be suggested. The blocking of magnetic fluctuations at low temperature with non Arrhenius slowing down makes think of spin glasses [29]. Note, however, that some spin glasses do not show a decrease but a growing of noise at low temperature due to UCF coupling [30].…”
Section: Noise Measurements As a Complementary Toolmentioning
confidence: 99%